Constitutionality of President’s Authority Regarding Lockdown Policy During the State’s Emergency - Deny Noer Wahid; Tasyabilla Pandi Utami; Febriansyah Ramadhan (Universitas Negeri Semarang, 2022)
The Article 22 of the 1945 Constitution of the Republic of Indonesia grants an exclusive authority to the president enacted as